2019
DOI: 10.1002/jbmr.3934
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Severe Hypocalcemia After US-Guided Percutaneous Microwave Ablation of the Parathyroid Gland in Patients with Secondary Hyperparathyroidism

Abstract: Our aim was to identify potential risk factors associated with severe hypocalcemia (SH) after microwave ablation (MWA) in patients with secondary hyperparathyroidism (SHPT). This retrospective cross‐sectional study enrolled 204 consecutive patients (with 387 parathyroid glands) who underwent MWA between July 2015 and May 2018. Clinical parameters, laboratory indices, and parathyroid gland characteristics were analyzed to assess risk factors associated with SH after MWA. SH was defined as serum calcium level lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Hypocalcemia is the most common medical complication following PTX or thermal ablation. Our study showed that hypocalcemia usually occurred one week after MWA [15]. However, in patients undergoing TPTX, although the serum calcium level tended to fall immediately after the operation, there might be a delay up to 2 weeks before it reached its lowest level.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Hypocalcemia is the most common medical complication following PTX or thermal ablation. Our study showed that hypocalcemia usually occurred one week after MWA [15]. However, in patients undergoing TPTX, although the serum calcium level tended to fall immediately after the operation, there might be a delay up to 2 weeks before it reached its lowest level.…”
Section: Discussionmentioning
confidence: 52%
“…According to the previous studies, the incidence of postoperative hypocalcemia and SH in SHPT patients ranges from 70% to 90% and from 37% to 57%, respectively [12,13]. Hypocalcemia and SH were also common in 37.6% and 22.1% SHPT patients after MWA [14,15]. As the principles and strategies of these two surgical methods are completely different, the occurrence of postoperative hypocalcemia will have their own characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Microwave ablation, as a minimally invasive therapeutic approach causing parathyroid cells to lose their endocrine functionality, has been increasingly used to treat SHPT. [9][10][11][12][13] Our preliminary study also shows that microwave ablation could be an alternative for secondary hyperparathyroidism in patients with maintenance hemodialysis. The long-term superiority of microwave ablation, however, should be clarified further.…”
Section: Introductionmentioning
confidence: 58%
“…We found that the postoperative low calcium level of patients was signi cantly correlated with the higher baseline bALP level. Previous analysis indicated that preoperative ALP level as a risk factor for hypocalcemia 5,18,19 . In our study, patients with baseline bALP concentration more than 115 U/L were prone to hypocalcemia, the sensitivity was 80.0%, and the speci city was 63.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, maintaining normal postoperative blood calcium is very important. Few studies have shown that preoperative alkaline phosphatase(ALP) 18 and PTH 19 levels are independent risk factors for postoperative SH in SHPT patients 5,20 .…”
mentioning
confidence: 99%